Validation and psychometric properties of the Depression Anxiety Stress Scale for Youth in Chinese adolescents - Jiang, Jian; Chen, Jianhua; Lin, Zhifeng; Tang, Xuwei; Hu, Zhijian (Frontiers in Psychology, 2024)
Introduction: Depression and anxiety are the most common mental health problems among adolescents. The Depression Anxiety Stress Scales for Youth (DASS-Y) is a newly developed instrument designed to assess these problems in adolescents. Aim: The present study aims to evaluate the psychometric properties of the DASS-Y among Chinese adolescents. Methods: A total of 326 secondary school students aged 14-18 years participated in the study. A convenience sampling method was adopted to conduct a test-retest of the DASS-Y among Chinese secondary school students. McDonald's omega, Cronbach's alpha, and intraclass correlation coefficient (ICC) along with their 95% CI were used to assess the internal consistency and test-retest reliability of the DASS-Y. Confirmatory Factor Analysis (CFA) evaluated the structural validity and convergent validity of the DASS-Y through the Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), Root Mean Square Error of Approximation (RMSEA), as well as Average Variance Extracted (AVE) and Composite Reliability (CR). Pearson correlation coefficients with the General Health Questionnaire-12 (GHQ-12), and the Pittsburgh Sleep Quality Index (PSQI) assessed criterion validity. Results: The CFA confirmed the validity the DASS-Y three-factor model consisting of depression, anxiety, and stress. The internal consistency reliability of the DASS-Y was found to be robust, with McDonald's omega and Cronbach's alpha values exceeding 0.8 for all dimensions across two measurements. The test-retest reliability was stable. The structural validity was reasonable and effective. Additionally, convergent validity is satisfactory, while criterion validity is also satisfactory. The three-factor model consisting of depression, anxiety and stress was confirmed through CFA.The DASS-Y exhibits satisfactory psychometric properties among Chinese secondary school adolescents, reliably and appropriately screening for mental health issues such as depression and anxiety within this population. Consequently, it can be employed as a standard tool for routine mental health surveillance in secondary schools.